Antistatic masterbatch, foaming material containing the antistatic masterbatch and preparation method thereof

Through the synergistic effect of the new conductive mica modification process and multi-component antistatic agent, the electrostatic problem of EVA foamed materials is solved, and a stable conductive network is formed in the porous structure, providing excellent antistatic effect.

CN119331420BActive Publication Date: 2025-04-22QUANZHOU ZUKANG BIOTECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411887665.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-22
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

EVA foaming materials have serious electrostatic problems in practical applications, mainly due to their highly insulating properties and porous structure, it is difficult for antistatic agents to form continuous conductive paths, and the conductive fillers are prone to agglomeration during foaming and the conductive paths are prone to disconnect.

Method used

By developing a new conductive mica modification process, it improves its compatibility with polymer matrix, and forms a stable conductive network through the synergistic effect of multi-component antistatic agents.

Benefits of technology

On the premise of ensuring foaming effect and mechanical properties, it provides excellent antistatic effects, solving the adverse impact of foaming structure on the formation of conductive networks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331420B_ABST
    Figure CN119331420B_ABST
Patent Text Reader

Abstract

The invention discloses an antistatic masterbatch, a foaming material containing the antistatic masterbatch and a preparation method, and relates to the technical field of foaming materials. The antistatic masterbatch is prepared from the following components: 50-80 parts of a polyether-polyolefin block copolymer, 10-20 parts of an alkyl sulfonate, 5-15 parts of a secondary alkyl sulfonate, 5-15 parts of a modification aid, 0.5-1 part of an antioxidant, 0.5-2 parts of a heat stabilizer and 1-3 parts of a dispersant; the antistatic masterbatch can solve the adverse effect of micropores of a foaming material on an antistatic agent, and can provide an excellent antistatic effect while ensuring a foaming effect and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foaming materials, and in particular to an antistatic masterbatch, a foaming material containing the antistatic masterbatch and a preparation method thereof. Background Art

[0002] Foaming material is a porous material with a large number of tiny bubbles, and has become an indispensable functional material in modern industry. It can be foamed by chemical foaming agents (such as azodicarbonamide, sodium bicarbonate, etc.) or physical foaming (such as CO2, N2 and other gases or low-boiling liquids). According to the different bubble structures, it can be divided into open-cell type (bubbles are interconnected) and closed-cell type (bubbles are independent of each other); according to the pore size, it can be divided into microporous foaming (pore size <100μm) and ordinary foaming (pore size >100μm).

[0003] EVA (ethylene-vinyl acetate copolymer) foaming materials are widely used in the industrial field due to their unique performance advantages. EVA molecular chains contain polar vinyl acetate groups, the content of which is generally 10-40%, and form a closed-cell porous structure after foaming. The material has excellent flexibility and elasticity, good weather resistance and aging resistance, low hardness and density, as well as excellent cushioning and shock absorption performance and excellent thermal insulation and sound insulation performance. At present, EVA foaming materials have been widely used in shoe materials (such as sports shoe midsoles, casual shoe soles), packaging (such as shockproof packaging, thermal insulation packaging), building materials (such as thermal insulation materials, waterproof materials), automobiles (such as sealing strips, shockproof pads) and electronics (such as cushioning materials, insulation materials) and other fields.

[0004] However, EVA foam materials face serious static electricity problems in practical applications. This is mainly due to the high insulation properties of EVA itself, and the foaming structure increases the specific surface area, which is very easy to generate static electricity during production and use. Environmental factors such as changes in temperature and humidity can also affect the generation and accumulation of static electricity. This static electricity will not only cause dust to be adsorbed on the surface of the product, affecting the appearance quality, but also interfere with the normal operation of production equipment, and may even cause fire hazards or interfere with the operation of electronic equipment.

[0005] At present, the methods for improving the antistatic properties of EVA foam materials mainly include adding antistatic agents, modifying conductive fillers and surface treatment. Commonly used antistatic agents include cationic types such as quaternary ammonium salts and amines, anionic types such as alkyl sulfonates and alkyl phosphates, and non-ionic types such as polyethers and fatty acid esters. Conductive fillers include inorganic fillers such as conductive carbon black, metal powder, conductive mica, and organic fillers such as conductive polymers, graphene, and carbon nanotubes. In addition, surface treatment technologies such as plasma treatment, conductive coating, and chemical modification can also be used.

[0006] CN113429653A discloses an antistatic EVA foam material and a preparation method thereof. The foam material comprises 10-14 parts of EVA resin, 1-5 parts of POE resin, 30-40 parts of PE resin, 20-30 parts of light calcium powder, 10-14 parts of carbon black, 0.396-0.4 parts of cross-linking agent, 0.92-0.98 parts of foaming agent, 0.8-0.86 parts of zinc oxide, 0.83-0.89 parts of zinc stearate, and 5-10 parts of antistatic agent.

[0007] However, there are still many problems with the prior art. The most prominent one is that there are a large number of tiny bubbles in the foaming material. This porous structure makes it difficult for the antistatic agent to form a continuous conductive path, and the bubbles block the charge transmission path. Traditional small molecule antistatic agents are easily enriched on the inner wall of the bubbles during the foaming process, and the foaming structure hinders their migration; the increased specific surface area of ​​the bubbles also accelerates the loss of the antistatic agent. For conductive fillers, the fillers are prone to agglomeration during the foaming process, the bubble structure makes the conductive path easy to disconnect, and too high a filler content will significantly affect the foaming performance. In addition, how to balance the foaming performance with the formation of the conductive network, and coordinate the material fluidity and filler dispersibility are also difficulties in formula design.

[0008] Therefore, it is of great significance to develop a technical solution that can construct a stable and effective conductive path in the porous structure of the foamed material. The present invention develops a new conductive mica modification process to improve its compatibility with the polymer matrix, and through the synergistic effect of a multi-component antistatic agent, successfully solves the adverse effect of the foamed structure on the formation of the conductive network, providing an innovative solution for the development of antistatic foamed materials. Summary of the invention

[0009] In order to solve the deficiencies in the prior art, the purpose of the present invention is to provide an antistatic masterbatch, a foaming material containing the antistatic masterbatch and a preparation method. The new antistatic agent can solve the adverse effects of the micropores of the foaming material on the antistatic masterbatch, and can provide excellent antistatic effect while ensuring the foaming effect and mechanical properties.

[0010] In order to achieve the above object, the present invention adopts the following technical solution:

[0011] An antistatic masterbatch is prepared from the following components by weight: 50-80 parts of a polyether-polyolefin block copolymer, 10-20 parts of an alkyl sulfonate, 5-15 parts of a secondary alkyl sulfonate, 5-15 parts of a modification aid, 0.5-1 parts of an antioxidant, 0.5-2 parts of a heat stabilizer, and 1-3 parts of a dispersant.

[0012] Preferably, the preparation method of the modification aid comprises the following steps:

[0013] (1) dispersing conductive mica in hydrochloric acid, stirring, filtering, washing, and drying to obtain activated conductive mica;

[0014] Mica surface activation process: Conductive mica is stirred in hydrochloric acid, and HCl undergoes a replacement reaction with the metal ions on the mica surface, converting the surface Si-O-M+ structure into a Si-OH structure, while removing surface impurities and increasing the surface hydroxyl content and active sites. This activation process provides the necessary reaction sites for subsequent surface modification.

[0015] Preferably, in step (1), the concentration of hydrochloric acid is 0.1-1 mol / L, the stirring condition is stirring at room temperature for 3-6 hours, and the drying condition is vacuum drying at 60-80°C for 10-14 hours.

[0016] (2) adding activated conductive mica and anhydrous ferric chloride to tetrahydrofuran, ultrasonically treating, uniformly mixing thiophene, thiophene methanol, hexadecyltrimethylammonium bromide, polyethylene glycol monomethyl ether, and deionized water to prepare a thiophene monomer solution, then dropwise adding the thiophene monomer solution under a nitrogen atmosphere, stirring and mixing, heating to react, filtering, washing, and drying the product to obtain pre-modified conductive mica;

[0017] Conductive polymer modification process: The activated mica and FeCl3 are dispersed in tetrahydrofuran, and FeCl3 is used as an oxidant to initiate the oxidative polymerization of thiophene. Under the action of the oxidant, the thiophene monomer loses electrons to form free radical cations, and then a polymerization reaction occurs. Among them, the hydroxyl groups of thiophene methanol form hydrogen bonds with the hydroxyl groups on the mica surface, which enhances the bonding between polythiophene and the mica surface; hexadecyltrimethylammonium bromide is used as a surfactant to reduce interfacial tension and promote the adsorption and uniform dispersion of thiophene monomers on the mica surface; polyethylene glycol monomethyl ether improves the dispersibility of the product through steric hindrance effect. Low temperature start-up ensures uniform nucleation, and the temperature increase reaction increases the degree of polymerization.

[0018] Preferably, in step (2), the amount ratio of activated conductive mica, anhydrous ferric chloride, tetrahydrofuran, thiophene, thiophene methanol, hexadecyltrimethylammonium bromide, polyethylene glycol monomethyl ether, and deionized water is 10g: 20-30g: 150-200mL: 20-30g: 5-10g: 2-4g: 3-5g: 150-200mL.

[0019] Preferably, in step (2), the mixture is stirred at 0-5°C for 1-3 hours, and the temperature is raised to 45-55°C for further reaction for 16-24 hours; the product is washed with anhydrous ethanol and deionized water for 3-4 times each, and vacuum dried at 60-80°C for 10-14 hours.

[0020] (3) Dispersing the pre-modified conductive mica in tetrahydrofuran, adding triethylamine, adding palmitoyl chloride into tetrahydrofuran to obtain a tetrahydrofuran solution of palmitoyl chloride, slowly dropping it under a nitrogen atmosphere, stirring the reaction, filtering, washing, and drying the product to obtain a modified auxiliary agent.

[0021] Long-chain alkyl modification process: pre-modified conductive mica reacts with palmitoyl chloride in tetrahydrofuran, and palmitoyl chloride reacts with residual hydroxyl groups on the mica surface and hydroxyl groups on the polythiophene chain to undergo acylation, and triethylamine is used as an acid-binding agent to eliminate HCl generated by the reaction. By introducing long-chain alkyl esters, the compatibility of conductive mica with the polymer matrix is ​​significantly improved.

[0022] Preferably, in step (3), the amount ratio of pre-modified conductive mica, tetrahydrofuran, triethylamine, and tetrahydrofuran solution of palmitoyl chloride is 10 g: 150-200 mL: 8-12 g: 100-150 mL; the tetrahydrofuran solution of palmitoyl chloride is prepared by using 15-20 g of palmitoyl chloride to make 100-150 mL of solution; the stirring reaction conditions are reaction at room temperature for 3-6 hours; and washing with anhydrous tetrahydrofuran 3-4 times.

[0023] Preferably, the carbon chain length of the alkyl sulfonate is C1-C10; the carbon chain length of the secondary alkyl sulfonate is C14-C17.

[0024] Preferably, the antioxidant is antioxidant 1010 and / or antioxidant 168; the heat stabilizer is calcium stearate and / or zinc stearate; and the dispersant is polyethylene wax.

[0025] The present invention also claims protection for a method for preparing an antistatic masterbatch, comprising the following steps: preparing 50-80 parts of a polyether-polyolefin block copolymer, 10-20 parts of an alkyl sulfonate, 5-15 parts of a secondary alkyl sulfonate, 5-15 parts of a modifying aid, 0.5-1 part of an antioxidant, 0.5-2 parts of a heat stabilizer, and 1-3 parts of a dispersant by weight, putting the mixture into a high-speed mixer and mixing for 2-6 minutes, discharging the mixture, and extruding and granulating the mixture using a twin-screw extruder at 150-200° C. and a screw speed of 25-50 Hz to obtain the antistatic masterbatch.

[0026] The present invention also claims protection for a foaming material, comprising the antistatic masterbatch, which is made of the following components, in parts by weight: 40-60 parts of EVA, 10-20 parts of polyolefin elastomer, 5-10 parts of EPDM rubber, 5-25 parts of styrene polymer, 4-6 parts of antistatic masterbatch, 2-5 parts of azodicarbonamide, 0.5-3 parts of stearic acid, and 0.2-1 parts of 1,4-di-tert-butylperoxyisopropylbenzene.

[0027] The present invention also claims protection for a method for preparing the foaming material, comprising the following steps: mixing the raw materials evenly and placing them in a preheated internal mixer at a temperature of 95-115°C for 7-10 minutes; refining the resulting mixture in an open mixer, transferring the mixture to a single-screw granulator for extrusion granulation, placing the granulated particles in a preheated flat vulcanizer mold cavity, and performing mold foaming at 2-12 MPa and 180-185°C for 7-10 minutes to obtain the foaming material.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention provides an antistatic masterbatch, which can form a stable conductive network through the synergistic effect of multiple components. Among them, the polyether-polyolefin block copolymer is used as the base resin, and its polyether segment has hydrophilicity and certain conductivity, which is conducive to the transmission and dissipation of charges; alkyl sulfonate and secondary alkyl sulfonate are used as ionic antistatic agents to synergistically construct a fast charge transmission channel; modified conductive mica provides a stable conductive skeleton, which effectively solves the blocking effect of the foaming structure on the conductive network.

[0030] 2. The present invention provides a modified additive, which not only gives the antistatic masterbatch excellent conductivity and dispersion stability, but also achieves a lasting antistatic effect in the foaming material through the synergistic effect of multiple components. First, the Si-OM + The structure is converted into Si-OH structure, which increases the surface hydroxyl content and active sites, and provides necessary reaction sites for subsequent modification; secondly, conductive polythiophene is in situ polymerized on the surface, in which the hydroxyl groups of thiophene methanol form hydrogen bonds with the hydroxyl groups on the mica surface, which enhances the binding force between polythiophene and the mica surface. At the same time, the synergistic effect of cationic and non-ionic surfactants is used to improve the dispersion stability. One end of polythiophene forms a stable connection with the mica surface to provide continuous conductivity, and the other end penetrates into the EVA macromolecular network through the subsequent introduction of long-chain alkyl to form a bridging structure, which gives good mechanical recovery; finally, the introduced ester-containing alkyl chain produces a strong interaction with the vinyl acetate group in the EVA molecular chain through the polar group, and the hydrophobic alkyl segment is compatible with the ethylene segment of EVA. This dual effect significantly improves the dispersibility of the conductive mica and prevents agglomeration during the foaming process. At the same time, the hydrophobicity of the long-chain alkyl reduces the adsorption of the conductive mica surface on the polar foaming agent, which is beneficial to the uniform decomposition of the foaming agent and the bubble nucleation, and improves the overall mechanical properties and buffer resilience of the material.

[0031] 3. The present invention provides a foaming material, which is prepared by a chemical foaming process using a multi-component blending system of EVA, polyolefin elastomer and styrene polymer. EVA provides excellent flexibility and elasticity, polyolefin elastomer enhances the toughness and impact resistance of the material, and styrene polymer improves the rigidity and dimensional stability of the material. The flaky structure of the conductive mica in the antistatic agent not only helps to form a conductive network, but also effectively blocks the infiltration of moisture in the air, giving the material excellent conductivity and anti-corrosion properties. The antistatic masterbatch is prepared by modifying the conductive mica and compounding it with a carrier resin and an ionic antistatic agent, which solves the problem of poor dispersibility of the conductive mica in the resin, avoids the degradation of mechanical properties caused by excessive addition, and achieves excellent antistatic effect while ensuring the foaming performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show schematic diagrams of certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 The antistatic masterbatch sheet prepared in Example 1 of the present invention;

[0034] Figure 2 The EVA foamed shoe material prepared in Example 1 of the present invention;

[0035] Figure 3 The EVA foamed shoe material prepared in Example 1 of the present invention;

[0036] Figure 4 The finished shoes are made using the EVA foamed shoe material prepared in Example 1. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0038] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.

[0039] The polyether-polyolefin block copolymer was PELECTRON AS from Sanyo Chemical of Japan;

[0040] The conductive mica particle size was 3000 mesh and was purchased from Shenzhen Haiyang Powder Technology Co., Ltd., product model HYP000074;

[0041] EVA was purchased from Formosa Plastics Corporation, model EVA7360M, EVA7470M;

[0042] Polyolefin elastomer (POE) was purchased from Dow, model POE8180, POE8150;

[0043] Ethylene propylene diene monomer (EPDM) was purchased from Dow, model EPDM 5565, EPDM 3745;

[0044] Styrene polymers were purchased from Asahi Kasei Corporation, models SBBS J1083 and SOE L609.

[0045] A method for preparing a foaming material containing an antistatic agent comprises the following steps:

[0046] (1) Dispersing the conductive mica in 0.1-1 mol / L hydrochloric acid, stirring at room temperature for 3-6 hours, filtering, washing, and vacuum drying at 60-80°C for 10-14 hours to obtain activated conductive mica;

[0047] (2) Add 10 g of activated conductive mica and 20-30 g of anhydrous ferric chloride to 150-200 mL of tetrahydrofuran, and perform ultrasonic treatment. Evenly mix 20-30 g of thiophene, 5-10 g of thiophene methanol, 2-4 g of hexadecyltrimethylammonium bromide, 3-5 g of polyethylene glycol monomethyl ether, and 150-200 mL of deionized water to prepare a thiophene monomer solution. Then, dropwise add the thiophene monomer solution under a nitrogen atmosphere, stir and mix at 0-5 °C for 1-3 h, heat to 45-55 °C, and continue to react for 16-24 h. Filter the product, wash with anhydrous ethanol and deionized water for 3-4 times each, and vacuum dry at 60-80 °C for 10-14 h to obtain pre-modified conductive mica.

[0048] (3) Disperse 10 g of pre-modified conductive mica in 150-200 mL of tetrahydrofuran, add 8-12 g of triethylamine, and prepare 100-150 mL of solution with 15-20 g of palmitoyl chloride. Slowly add dropwise under a nitrogen atmosphere, stir and react at room temperature for 3-6 h, filter the product, wash it with anhydrous tetrahydrofuran for 3-4 times, and dry it to obtain a modified auxiliary agent;

[0049] (4) Prepare 50-80 parts of polyether-polyolefin block copolymer, 10-20 parts of alkyl sulfonate, 5-15 parts of secondary alkyl sulfonate, 5-15 parts of modification aid, 0.5-1 part of antioxidant, 0.5-2 parts of heat stabilizer, and 1-3 parts of dispersant by weight, put them into a high-speed mixer and mix them for 2-6 minutes, discharge them, and extrude and granulate them with a twin-screw extruder at 150-200° C. and a screw speed of 25-50 Hz to obtain the antistatic masterbatch;

[0050] (5) Take 40-60 parts of EVA, 10-20 parts of polyolefin elastomer, 5-10 parts of ethylene propylene diene monomer rubber, 5-25 parts of styrene polymer, 4-6 parts of antistatic masterbatch, 2-5 parts of azodicarbonamide, 0.5-3 parts of stearic acid, and 0.2-1 part of 1,4-di-tert-butylperoxyisopropylbenzene, mix the raw materials evenly, and place them in a preheated internal mixer at a temperature of 95-115° C. for 7-10 minutes; after the obtained mixture is opened in an open mixer, it is transferred to a single-screw granulator for extrusion granulation, and the granulated particles are placed in a preheated flat vulcanizer mold cavity, and molded for foaming at 2-12 MPa and 180-185° C. for 7-10 minutes to obtain the foamed material.

[0051] The carbon chain length of the alkyl sulfonate is C1-C10; the carbon chain length of the secondary alkyl sulfonate is C14-C17; the antioxidant is antioxidant 1010 and / or antioxidant 168; the heat stabilizer is calcium stearate and / or zinc stearate; and the dispersant is polyethylene wax.

[0052] The present invention will be further described below through specific embodiments.

[0053] Example 1

[0054] A method for preparing a foaming material containing an antistatic agent comprises the following steps:

[0055] (1) Dispersing the conductive mica in 0.5 mol / L hydrochloric acid, stirring at room temperature for 5 h, filtering, washing with deionized water until neutral, and vacuum drying at 70°C for 12 h to obtain activated conductive mica;

[0056] (2) Add 10 g of activated conductive mica and 30 g of anhydrous ferric chloride to 200 mL of tetrahydrofuran, and perform ultrasonic treatment. Mix 30 g of thiophene, 10 g of 3-thiophene methanol, 4 g of hexadecyltrimethylammonium bromide, 5 g of polyethylene glycol monomethyl ether, and 200 mL of deionized water to prepare a thiophene monomer solution. Then, add the thiophene monomer solution dropwise under a nitrogen atmosphere, stir and mix at 5°C for 1 h, heat to 55°C and continue to react for 16 h. Filter the product, wash it with anhydrous ethanol and deionized water for 3 times each, and vacuum dry it at 70°C for 12 h to obtain pre-modified conductive mica.

[0057] (3) Disperse 10 g of pre-modified conductive mica in 200 mL of tetrahydrofuran, add 12 g of triethylamine, and prepare a 150 mL solution with 20 g of palmitoyl chloride. Slowly dropwise add the solution under a nitrogen atmosphere, stir and react at room temperature for 6 h, filter the product, wash it with anhydrous tetrahydrofuran for 3 times, and dry it to obtain a modified auxiliary agent.

[0058] (4) Prepare 800 g of polyether-polyolefin block copolymer, 200 g of sodium octadecyl sulfonate, 150 g of secondary alkyl sodium tetradecyl sulfonate, 150 g of modification aid, 10 g of antioxidant 1010, 20 g of heat stabilizer calcium stearate, and 30 g of dispersant polyethylene wax according to weight, put them into a high-speed mixer and mix them for 4 minutes, discharge the materials, and extrude and granulate them using a twin-screw extruder at 180° C. and a screw speed of 40 Hz to obtain the antistatic masterbatch;

[0059] (5) Take 600 g of EVA, 200 g of polyolefin elastomer, 100 g of EPDM rubber, 250 g of styrene polymer, 60 g of antistatic masterbatch, 50 g of azodicarbonamide, 30 g of stearic acid, and 10 g of 1,4-di-tert-butylperoxyisopropylbenzene, mix the raw materials evenly, and place them in a preheated internal mixer at a temperature of 105° C. for internal mixing for 8 min; after the obtained mixture is mixed in an open mixer, it is transferred to a single-screw granulator for extrusion granulation, and the granulated particles are placed in a preheated flat vulcanizer mold cavity, and molded and foamed at 7 MPa and 183° C. for 8 min to obtain the foamed material.

[0060] Example 2

[0061] A method for preparing a foaming material containing an antistatic agent comprises the following steps:

[0062] (1) Dispersing the conductive mica in 0.5 mol / L hydrochloric acid, stirring at room temperature for 5 h, filtering, washing with deionized water until neutral, and vacuum drying at 70°C for 12 h to obtain activated conductive mica;

[0063] (2) 10 g of activated conductive mica and 26 g of anhydrous ferric chloride were added to 200 mL of tetrahydrofuran and ultrasonically treated. 26 g of thiophene, 8 g of 3-thiophene methanol, 3 g of hexadecyltrimethylammonium bromide, 4-polyethylene glycol monomethyl ether, and 200 mL of deionized water were mixed evenly to prepare a thiophene monomer solution. Subsequently, the thiophene monomer solution was added dropwise under a nitrogen atmosphere, stirred and mixed at 4°C for 2 h, heated to 50°C and continued to react for 18 h, the product was filtered, washed with anhydrous ethanol and deionized water for 3 times each, and vacuum dried at 70°C for 12 h to obtain pre-modified conductive mica;

[0064] (3) Disperse 10 g of pre-modified conductive mica in 200 mL of tetrahydrofuran, add 10 g of triethylamine, and prepare 150 mL of solution with 18 g of palmitoyl chloride. Slowly add dropwise under a nitrogen atmosphere, stir and react at room temperature for 5 h, filter the product, wash it 3 times with anhydrous tetrahydrofuran, and dry it to obtain a modified auxiliary agent;

[0065] (4) Prepare 700 g of polyether-polyolefin block copolymer, 180 g of sodium octadecyl sulfonate, 120 g of sodium tetradecyl sulfonate, 120 g of modifying aid, 8 g of antioxidant 1010, 15 g of heat stabilizer calcium stearate, and 25 g of dispersant polyethylene wax according to weight, put them into a high-speed mixer and mix them for 4 min, discharge the materials, and extrude and granulate them using a twin-screw extruder at 180° C. and a screw speed of 40 Hz to obtain the antistatic masterbatch;

[0066] (5) Take 540 g of EVA, 180 g of polyolefin elastomer, 80 g of EPDM rubber, 200 g of styrene polymer, 50 g of antistatic masterbatch, 40 g of azodicarbonamide, 25 g of stearic acid, and 8 g of 1,4-di-tert-butylperoxyisopropylbenzene, mix the raw materials evenly, and place them in a preheated internal mixer at a temperature of 105° C. for internal mixing for 8 min; after the obtained mixture is mixed in an open mixer, it is transferred to a single-screw granulator for extrusion granulation, and the granulated particles are placed in a preheated flat vulcanizer mold cavity, and molded and foamed at 7 MPa and 183° C. for 8 min to obtain the foamed material.

[0067] Example 3

[0068] A method for preparing a foaming material containing an antistatic agent comprises the following steps:

[0069] (1) Dispersing the conductive mica in 0.5 mol / L hydrochloric acid, stirring at room temperature for 5 h, filtering, washing with deionized water until neutral, and vacuum drying at 70°C for 12 h to obtain activated conductive mica;

[0070] (2) 10 g of activated conductive mica and 24 g of anhydrous ferric chloride were added to 200 mL of tetrahydrofuran and ultrasonically treated. 24 g of thiophene, 7 g of 3-thiophene methanol, 3 g of hexadecyltrimethylammonium bromide, 4 g of polyethylene glycol monomethyl ether, and 200 mL of deionized water were mixed evenly to prepare a thiophene monomer solution. Subsequently, the thiophene monomer solution was added dropwise under a nitrogen atmosphere, stirred and mixed at 2°C for 2 h, and the temperature was raised to 50°C to continue the reaction for 20 h. The product was filtered, washed with anhydrous ethanol and deionized water for 3 times each, and vacuum dried at 70°C for 12 h to obtain pre-modified conductive mica.

[0071] (3) Disperse 10 g of pre-modified conductive mica in 200 mL of tetrahydrofuran, add 10 g of triethylamine, and prepare 150 mL of solution with 16 g of palmitoyl chloride. Slowly dropwise add the solution under nitrogen atmosphere, stir and react at room temperature for 4 h, filter the product, wash it with anhydrous tetrahydrofuran for 3 times, and dry it to obtain a modified auxiliary agent.

[0072] (4) Prepare 600 g of polyether-polyolefin block copolymer, 140 g of sodium octadecyl sulfonate, 100 g of sodium tetradecyl sulfonate, 100 g of modifying aid, 6 g of antioxidant 1010, 10 g of heat stabilizer calcium stearate, and 15 g of dispersant polyethylene wax according to weight, put them into a high-speed mixer and mix them for 4 min, discharge the materials, and extrude and granulate them using a twin-screw extruder at 180° C. and a screw speed of 40 Hz to obtain the antistatic masterbatch;

[0073] (5) Take 450g of EVA, 120g of polyolefin elastomer, 70g of EPDM rubber, 100g of styrene polymer, 40g of antistatic masterbatch, 30g of azodicarbonamide, 10g of stearic acid and 6g of 1,4-di-tert-butylperoxyisopropylbenzene, mix the raw materials evenly and place them in a preheated internal mixer at a temperature of 105°C for 8min; after the obtained mixture is opened in an open mixer, it is transferred to a single-screw granulator for extrusion granulation, and the granulated particles are placed in a preheated flat vulcanizer mold cavity, and molded and foamed at 7MPa and 183°C for 8min to obtain the foamed material.

[0074] Example 4

[0075] A method for preparing a foaming material containing an antistatic agent comprises the following steps:

[0076] (1) Dispersing the conductive mica in 0.5 mol / L hydrochloric acid, stirring at room temperature for 5 h, filtering, washing with deionized water until neutral, and vacuum drying at 70°C for 12 h to obtain activated conductive mica;

[0077] (2) Add 10 g of activated conductive mica and 20 g of anhydrous ferric chloride to 200 mL of tetrahydrofuran, and perform ultrasonic treatment. Mix 20 g of thiophene, 5 g of 3-thiophene methanol, 2 g of hexadecyltrimethylammonium bromide, 3 g of polyethylene glycol monomethyl ether, and 200 mL of deionized water to prepare a thiophene monomer solution. Then, add the thiophene monomer solution dropwise under a nitrogen atmosphere, stir and mix at 0°C for 3 h, heat to 45°C and continue to react for 24 h. Filter the product, wash it with anhydrous ethanol and deionized water for 3 times each, and vacuum dry it at 70°C for 12 h to obtain pre-modified conductive mica.

[0078] (3) Disperse 10 g of pre-modified conductive mica in 200 mL of tetrahydrofuran, add 8 g of triethylamine, and prepare 150 mL of solution with 15 g of palmitoyl chloride. Slowly dropwise add the solution under nitrogen atmosphere, stir and react at room temperature for 3 h, filter the product, wash it 3 times with anhydrous tetrahydrofuran, and dry it to obtain a modified auxiliary agent.

[0079] (4) Prepare 500 g of polyether-polyolefin block copolymer, 100 g of sodium octadecyl sulfonate, 50 g of secondary alkyl sodium tetradecyl sulfonate, 50 g of modifying aid, 5 g of antioxidant 1010, 5 g of heat stabilizer calcium stearate, and 10 g of dispersant polyethylene wax according to weight, put them into a high-speed mixer and mix them for 4 minutes, discharge the materials, and extrude and granulate them using a twin-screw extruder at 180° C. and a screw speed of 40 Hz to obtain the antistatic masterbatch;

[0080] (5) Take 400 g of EVA, 100 g of polyolefin elastomer, 50 g of EPDM rubber, 50 g of styrene polymer, 40 g of antistatic masterbatch, 20 g of azodicarbonamide, 5 g of stearic acid, and 2 g of 1,4-di-tert-butylperoxyisopropylbenzene, mix the raw materials evenly, and place them in a preheated internal mixer at a temperature of 105°C for internal mixing for 8 minutes; after the obtained mixture is mixed in an open mixer, it is transferred to a single-screw granulator for extrusion granulation, and the granulated particles are placed in a preheated flat vulcanizer mold cavity, and molded and foamed at 7 MPa and 183°C for 8 minutes to obtain the foamed material.

[0081] Comparative Example 1

[0082] A method for preparing a foaming material containing an antistatic agent comprises the following steps:

[0083] (1) Dispersing the conductive mica in 0.5 mol / L hydrochloric acid, stirring at room temperature for 5 h, filtering, washing with deionized water until neutral, and vacuum drying at 70°C for 12 h to obtain activated conductive mica;

[0084] (2) Add 10 g of activated conductive mica and 30 g of anhydrous ferric chloride to 200 mL of tetrahydrofuran, and perform ultrasonic treatment. Mix 30 g of thiophene, 10 g of 3-thiophene methanol, 4 g of hexadecyltrimethylammonium bromide, 5 g of polyethylene glycol monomethyl ether, and 200 mL of deionized water to prepare a thiophene monomer solution. Then, add the thiophene monomer solution dropwise under a nitrogen atmosphere, stir and mix at 5°C for 1 h, heat to 55°C and continue to react for 16 h. Filter the product, wash it with anhydrous ethanol and deionized water for 3 times each, and vacuum dry it at 70°C for 12 h to obtain pre-modified conductive mica.

[0085] (3) Prepare 800 g of polyether-polyolefin block copolymer, 200 g of sodium octadecyl sulfonate, 150 g of sodium tetradecyl sulfonate, 150 g of pre-modified conductive mica, 10 g of antioxidant 1010, 20 g of heat stabilizer calcium stearate, and 30 g of dispersant polyethylene wax according to weight, put them into a high-speed mixer and mix them for 4 minutes, discharge the materials, and extrude and granulate them using a twin-screw extruder at 180° C. and a screw speed of 40 Hz to obtain an antistatic masterbatch;

[0086] (4) Take 600g of EVA, 200g of polyolefin elastomer, 100g of EPDM rubber, 250g of styrene polymer, 60g of antistatic masterbatch, 50g of azodicarbonamide, 30g of stearic acid and 10g of 1,4-di-tert-butylperoxyisopropylbenzene, mix the raw materials evenly and place them in a preheated internal mixer at a temperature of 105°C for 8min; after the obtained mixture is opened in an open mixer, it is transferred to a single-screw granulator for extrusion granulation, and the granulated particles are placed in a preheated flat vulcanizer mold cavity, and molded and foamed at 7MPa and 183°C for 8min to obtain the foamed material.

[0087] Comparative Example 2

[0088] A method for preparing a foaming material containing an antistatic agent comprises the following steps:

[0089] (1) Dispersing the conductive mica in 0.5 mol / L hydrochloric acid, stirring at room temperature for 5 h, filtering, washing with deionized water until neutral, and vacuum drying at 70°C for 12 h to obtain activated conductive mica;

[0090] (2) Prepare 800 g of polyether-polyolefin block copolymer, 200 g of sodium octadecyl sulfonate, 150 g of sodium tetradecyl sulfonate, 150 g of activated conductive mica, 10 g of antioxidant 1010, 20 g of heat stabilizer calcium stearate, and 30 g of dispersant polyethylene wax according to weight, put them into a high-speed mixer and mix them for 4 minutes, discharge the materials, and extrude and granulate them using a twin-screw extruder at 180° C. and a screw speed of 40 Hz to obtain an antistatic masterbatch;

[0091] (3) Take 600g of EVA, 200g of polyolefin elastomer, 100g of EPDM rubber, 250g of styrene polymer, 60g of antistatic masterbatch, 50g of azodicarbonamide, 30g of stearic acid and 10g of 1,4-di-tert-butylperoxyisopropylbenzene, mix the raw materials evenly and place them in a preheated internal mixer at a temperature of 105°C for 8min; after the obtained mixture is opened in an open mixer, it is transferred to a single-screw granulator for extrusion granulation, and the granulated particles are placed in a preheated flat vulcanizer mold cavity, and molded and foamed at 8MPa and 183°C for 8min to obtain the foamed material.

[0092] Comparative Example 3

[0093] A method for preparing a foaming material comprises the following steps:

[0094] Take 600g of EVA, 200g of polyolefin elastomer, 100g of ethylene propylene rubber, 250g of styrene polymer, 50g of azodicarbonamide, 30g of stearic acid and 10g of 1,4-di-tert-butylperoxyisopropylbenzene, mix the raw materials evenly and place them in a preheated internal mixer at a temperature of 105°C for 8min; after the obtained mixture is opened in an open mixer, it is transferred to a single-screw granulator for extrusion granulation, and the granulated particles are placed in a preheated flat vulcanizer mold cavity, and molded and foamed at 8MPa and 180°C for 8min to obtain the foamed material.

[0095] The performance tests of the foamed materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were conducted, and the apparent density was tested with reference to GB / T 6343-2009 "Determination of apparent density of foam plastics and rubbers"; the Shore C hardness was tested with reference to GB / T 531.1-2008 "Test method for indentation hardness of vulcanized rubber or thermoplastic rubber Part 1: Shore durometer method (Shore hardness)"; the falling ball elasticity was tested with reference to GB / T 6670-2008 "Determination of rebound properties of soft foam polymer materials by falling ball method"; the tensile strength and elongation at break were tested with reference to GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber"; and the volume resistivity was tested with reference to GB / T 31838.2-2019 "Dielectric and resistive properties of solid insulating materials Part 2: Resistivity properties (DC method) Volume resistance and volume resistivity". Specific data are shown in Table 1.

[0096] Table 1 Foam material performance test results

[0097] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Apparent density (g / cm 3 )]]> 0.265 0.257 0.252 0.244 0.269 0.271 0.235 Shore C hardness (degrees) 49 48 46 45 51 57 46 Drop ball elasticity (%) 58 61 62 68 54 48 66 Tensile strength(MPa) 2.73 2.69 2.68 2.64 2.52 2.23 2.41 Elongation at break (%) 489 482 478 471 456 413 437 Volume resistivity (Ω·cm) <![CDATA[4.3×10 8 ]]> <![CDATA[2.5×10 8 ]]> <![CDATA[1.9×10 8 ]]> <![CDATA[1.3×10 8 ]]> <![CDATA[8.5×10 8 ]]> <![CDATA[1.7×10 10 ]]> <![CDATA[2.2×10 12 ]]>

[0098] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An antistatic masterbatch, characterized in that: The invention is prepared from the following components by weight: 50-80 parts of polyether-polyolefin block copolymer, 10-20 parts of alkyl sulfonate, 5-15 parts of secondary alkyl sulfonate, 5-15 parts of modification aid, 0.5-1 parts of antioxidant, 0.5-2 parts of heat stabilizer and 1-3 parts of dispersant; The preparation method of the modified auxiliary agent comprises the following steps: (1) dispersing conductive mica in hydrochloric acid, stirring, filtering, washing, and drying to obtain activated conductive mica; (2) adding activated conductive mica and anhydrous ferric chloride to tetrahydrofuran, ultrasonically treating, uniformly mixing thiophene, thiophene methanol, hexadecyltrimethylammonium bromide, polyethylene glycol monomethyl ether, and deionized water to prepare a thiophene monomer solution, then dropwise adding the thiophene monomer solution under a nitrogen atmosphere, stirring and mixing, heating to react, filtering, washing, and drying the product to obtain pre-modified conductive mica; (3) Dispersing the pre-modified conductive mica in tetrahydrofuran, adding triethylamine, adding palmitoyl chloride into tetrahydrofuran to obtain a tetrahydrofuran solution of palmitoyl chloride, slowly dropping it under a nitrogen atmosphere, stirring the reaction, filtering, washing, and drying the product to obtain a modified auxiliary agent.

2. The antistatic masterbatch according to claim 1, characterized in that: In step (1), the concentration of hydrochloric acid is 0.1-1 mol / L, the stirring condition is stirring at room temperature for 3-6 hours, and the drying condition is vacuum drying at 60-80°C for 10-14 hours.

3. The antistatic masterbatch according to claim 1, characterized in that: In step (2), the dosage ratio of activated conductive mica, anhydrous ferric chloride, tetrahydrofuran, thiophene, thiophene methanol, hexadecyltrimethylammonium bromide, polyethylene glycol monomethyl ether, and deionized water is 10g: 20-30g: 150-200mL: 20-30g: 5-10g: 2-4g: 3-5g: 150-200mL.

4. The antistatic masterbatch according to claim 1, characterized in that: In step (2), the mixture is stirred at 0-5°C for 1-3 hours, and the temperature is raised to 45-55°C to continue the reaction for 16-24 hours. The product is washed with anhydrous ethanol and deionized water for 3-4 times each, and vacuum dried at 60-80°C for 10-14 hours.

5. The antistatic masterbatch according to claim 1, characterized in that: In step (3), the amount ratio of pre-modified conductive mica, tetrahydrofuran, triethylamine, and tetrahydrofuran solution of palmitoyl chloride is 10 g: 150-200 mL: 8-12 g: 100-150 mL; the tetrahydrofuran solution of palmitoyl chloride is prepared by using 15-20 g of palmitoyl chloride to make 100-150 mL of solution; the stirring reaction condition is to react at room temperature for 3-6 hours; and the mixture is washed with anhydrous tetrahydrofuran 3-4 times.

6. The antistatic masterbatch according to claim 1, characterized in that: The carbon chain length of the alkyl sulfonate is C1-C10; the carbon chain length of the secondary alkyl sulfonate is C14-C17.

7. The antistatic masterbatch according to claim 1, characterized in that: The antioxidant is antioxidant 1010 and / or antioxidant 168; the heat stabilizer is calcium stearate and / or zinc stearate; and the dispersant is polyethylene wax.

8. A foaming material, characterized in that: The antistatic masterbatch comprising the antistatic masterbatch according to any one of claims 1 to 7 is made of the following components in parts by weight: 40 to 60 parts of EVA, 10 to 20 parts of polyolefin elastomer, 5 to 10 parts of EPDM rubber, 5 to 25 parts of styrene polymer, 4 to 6 parts of antistatic masterbatch, 2 to 5 parts of azodicarbonamide, 0.5 to 3 parts of stearic acid, and 0.2 to 1 part of 1,4-di-tert-butylperoxyisopropylbenzene.

9. A method for preparing a foamed material as claimed in claim 8, characterized in that: The method comprises the following steps: mixing the raw materials uniformly and placing them in a preheated internal mixer at a temperature of 95-115°C for 7-10 minutes; transferring the obtained mixture to a single-screw granulator for extrusion granulation after being mixed in an open mixer; placing the granulated particles in a preheated flat plate vulcanizer mold cavity, and performing mold compression foaming for 7-10 minutes at 2-12MPa and 180-185°C to obtain the foaming material.

Citation Information

Patent Citations

  • Antistatic EVA foaming material and preparation method thereof

    CN113429653A

  • Permanent anti-static electricity high-density polyethylene (HDPE) composite material and preparation method thereof

    CN103131069A

  • Polythiophene / organic micro-crystal muscovite conductive mineral material and preparing method thereof

    CN105754075A

  • Organic modified mica as well as preparation method and application thereof

    CN116554711A

  • Conductive sericite powder preparation method

    CN1765805A